Paratubal Cystectomy in a Pregnant Woman Using the Single-Incision Laparoscopic Surgery (SILS) Technique. (14th July 2022) - Nelson, Luke William; MacKenzie, Elliot
Abstract : Introduction . The proliferation of prenatal ultrasound has enhanced the detection of adnexal masses during pregnancy. The presentation necessitates a clear approach to investigation and treatment that balances both maternal and fetal risk. Laparoscopy is a safe approach to surgical management in the pregnant patient, and SILS may contribute to minimising perioperative complications. Case Presentation . We present the case of a 21-year-old female in her second trimester of pregnancy presenting with a large 20 cm right adnexal cyst. We proceeded with laparoscopic cystectomy via the SILS technique. There were no intraoperative complications, and she recovered well postoperatively. Conclusion . Laparoscopic resection of adnexal lesions is safe during pregnancy and should be favoured over the open approach. SILS minimises incision sites and has potential for reduction in perioperative morbidity.